2022
DOI: 10.2478/rtuect-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Sound Absorption: Dependence of Rubber Particles Impurities in Tyre Textile Fibre

Abstract: In recent years, the recycling of waste materials has become significant due to the movement of the European Union toward the Green Deal and the low impact on the environment. The paper studies the possibility of Waste Tyre Textile Fibre (WTTF) for sound absorption applications. WTTF is the material generated during the end-of-life tyre recycling process, which is separated from rubber and metal parts. In this study, three different types of WTTF samples were tested in which they consist of different levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The trace amounts of metals in waste tire-derived textile fibers influence the acoustic performance of their composite materials in sustainable building applications. The tiny amounts of impurities also decrease their sound absorption coefficient in insulation building applications [ 75 ]. PS and polyurethane (PU) foams are primarily for thermal insulation building components.…”
Section: Waste Tire-derived Recycled Filler-tailored Ps Compositesmentioning
confidence: 99%
“…The trace amounts of metals in waste tire-derived textile fibers influence the acoustic performance of their composite materials in sustainable building applications. The tiny amounts of impurities also decrease their sound absorption coefficient in insulation building applications [ 75 ]. PS and polyurethane (PU) foams are primarily for thermal insulation building components.…”
Section: Waste Tire-derived Recycled Filler-tailored Ps Compositesmentioning
confidence: 99%
“…Studies showed that it has potential, as its sound absorption coefficient (NRC value) was 0.56. Ružickij and Grubliauskas [36] made the first attempts to investigate the sound absorption coefficient of WTTF, and investigating the dependence of rubber remains on the sound absorption capability. They found out that an increase in rubber remains decreases sound absorption coefficient.…”
Section: Introductionmentioning
confidence: 99%